Inhibitors of HSP90 block p95-HER2 signaling in Trastuzumab-resistant tumors and suppress their growth - Chandarlapaty, Sarat (2009)
The anti-HER2 antibody Trastuzumab (Herceptin) has been proven to be effective in the treatment of HER2 overexpressing breast cancer; resistance, however invariably emerges in metastatic tumors. The expression of p95-HER2, a form of HER2 with a truncated extracellular domain that lacks the Trastuzumab binding epitope, has been implicated as a mechanism of resistance to the antibody. We utilized an in vivo tumor model that overexpresses p95-HER2 and demonstrate it to be resistant to the signaling and antitumor effects of Trastuzumab. We find that both full length and p95-HER2 interact with the HSP90 chaperone protein and are degraded in tumor cells exposed to HSP90 inhibitors in tissue culture and in vivo. Loss of expression of p95-HER2 is accompanied by downregulation of the PI3K/AKT and ERK signaling pathways and inhibition of cell proliferation. Chronic administration of HSP90 inhibitors in vivo results in sustained loss of HER2 and p95-HER2 expression and inhibition of AKT activation together with induction of apoptosis and complete inhibition of tumor growth in Trastuzumab-resistant, p95-HER2-overexpressing models. Thus, p95-HER2 is an HSP90 client protein, the expression and function of which can be effectively suppressed in vivo by HSP90 inhibitors. HSP90 inhibition is therefore a potentially effective therapeutic strategy for p95-HER2-mediated Trastuzumab-resistant breast cancer.